Biotechnological Advances in Enzymatic Hydrolysis and Fermentation for Edible Insects: Functionality, Acceptability and Safety - Mittal, Ravi K.; Krishna, Gaurav; Sharma, Vikram (Current Pharmaceutical Biotechnology, 2025)
ObjectivesThis review paper examines biotechnological methods for enhancing edible insects using enzymatic hydrolysis and fermentation. Evaluations involve improving functionality, analyzing consumer acceptability elements, guaranteeing safety and quality, negotiating regulatory frameworks, and suggesting field breakthroughs and applications.MethodsOur method comprises a thorough literature analysis and academic database searches for edible insect enzymatic hydrolysis and fermentation investigations. Based on gaps in the literature, we investigate edible insect safety, consumer acceptability, and legal and regulatory issues.ResultsThe results show biotechnological advances in enzymatic hydrolysis and fermentation for edible insect functioning. Sensory and cultural aspects affect consumer acceptability. To ensure edible insect product safety, hazards and pollutants are addressed. The legal analysis highlights compliance issues and possibilities.ConclusionThis review shows how enzymatic hydrolysis and fermentation improve edible insect functioning, safety, and nutrition. The review includes consumer acceptability dynamics, legal issues, and safety analysis.
Keywords: functionality